17β-Estradiol (E2) may be involved in the mode of crustacean female sex hormone (CFSH) action in the blue crab, Callinectes sapidus - Wang, Tao; He, Ke; Blaney, Lee; Chung, J. Sook (Frontiers in Endocrinology, 2022)
17β-estradiol (E2) has been proved to control reproduction, sexual differentiation, and the development of the secondary sexual characteristics of vertebrate females. In decapod crustacean species, crustacean female sex hormone (CFSH), a protein hormone, is required for developing adult-specific ovigerous setae for embryo brooding and gonophores for mating at the blue crab Callinectes sapidus puberty molting. However, it is unclear that whether the mode of CFSH action involves a vertebrate-type sex steroid hormone in crustaceans. To this end, E2 levels were first measured using a competitive ELISA in the hemolymph and the potential CFSH target tissues from both prepuberty and adult females; the presence of E2 was further confirmed with a liquid chromatography tandem mass spectrometry method. Then, the cDNAs of the following genes known to be associated with vertebrate steroidogenic pathways were isolated: StAR-related lipid transfer protein 3 (StAR3); 3β-hydroxysteroid dehydrogenase (3βHSD); two isoforms of 17β-hydroxysteroid dehydrogenase 8 (17βHSD8); and, estradiol-related receptor (ERR). RT-PCR analysis revealed that these genes were widely distributed in the eyestalk ganglia, hepatopancreas, brain, ovary, spermathecae, ovigerous and plumose setae tissues of adult females. The 17βHSD8 transcripts were localized in the follicle cells, the periphery of the nuclear membrane of primary oocytes, and yolk granules of the vitellogenic oocytes using in situ hybridization, and the corresponding protein was detected in the follicle cells and ooplasm of primary oocytes using immunohistochemistry. Furthermore, the adult females injected with CFSH-dsRNA (n = 30 times) had E2 and StAR3 transcripts levels lower in the ovigerous and plumose setae, spermathecae than controls. These results suggested that the mode of CFSH action in C. sapidus might involve E2 in these adult-female-specific tissues.